2013
DOI: 10.4103/0972-0707.120936
|View full text |Cite
|
Sign up to set email alerts
|

Sealing ability of three single-cone obturation systems: An in-vitro glucose leakage study

Abstract: Aim:The aim of this study is to compare the corono-apical sealing ability of three single-cone obturation systems using a glucose leakage model.Materials and Methods:A total of 90 extracted maxillary single rooted teeth were selected and their crowns were cut. The root canal of each sample was instrumented using a rotary crown down technique and then divided into four experimental (n = 20 each) and two control groups (n = 5 each). Samples in the experimental groups were filled as follows: Group 1, cold lateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 24 publications
(26 reference statements)
3
20
0
Order By: Relevance
“…Due to its property of expansion, instead of shrinkage, it provides better sealing ability. 10 In the present study, GuttaFlow showed lower mean value of dye penetration 0.655 ± 0.396 as compared with other experimental groups; thus, it has better apical sealing ability as compared with other groups. This was according to the results reported by Vyavahare et al 11 After GuttaFlow, Gp II (Thermafil) 0.918 ± 0.399 showed lesser microleakage as compared with Beefill and lateral condensation groups.…”
Section: Discussionsupporting
confidence: 41%
“…Due to its property of expansion, instead of shrinkage, it provides better sealing ability. 10 In the present study, GuttaFlow showed lower mean value of dye penetration 0.655 ± 0.396 as compared with other experimental groups; thus, it has better apical sealing ability as compared with other groups. This was according to the results reported by Vyavahare et al 11 After GuttaFlow, Gp II (Thermafil) 0.918 ± 0.399 showed lesser microleakage as compared with Beefill and lateral condensation groups.…”
Section: Discussionsupporting
confidence: 41%
“…In this regard, GuttaFlow presents post-setting expansion 7 and chemical bond with gutta-percha and root canal walls 8 , which could influence the filling of root canal space 24 with high percentage of gutta-percha--filled areas when used in the single-cone technique or with additional accessory gutta-percha cones 25 . The single-cone technique has become increasingly popular, especially in root canals prepared with rotary or reciprocating nickel-titanium systems 12,26 . The penetration of GuttaFlow 2 into ramifications of the main canal with the single-cone technique was not investigated here and should be considered in future research.…”
Section: Discussionmentioning
confidence: 99%
“…According to the manufacturer, this new endodontic sealer presents good physicochemical and antimicrobial properties 9 . However, it has been poorly investigated [10][11][12] and it should be further compared with existing materials. The AH Plus (DeTrey Dentsply GmbH, Konstanz, Germany) is based on epoxy resin and it is considered a goldstandard material for root filling due to its long history of clinical success 6 and remarkable bond strength to dentin 13 .…”
Section: Introductionmentioning
confidence: 99%
“…This study was carried out to evaluate clinically the technical quality of root canal treatment performed on adult patients attending the Faculty of Dentistry, University of Umm Alqura. A few studies (30) have used (in vivo) human teeth to evaluate the amount of voids in root canal fillings by CBCT, the present study was conducted on patient with variable teeth with the complex canal morphology to have more reliable results when measuring the percentage of void, Most previous studies that have evaluated filling quality used artificial teeth with a single canal and with few anatomical variations, these samples might not have anatomical structures that are present in human teeth, and don't reflect the complex root canal morphology encountered in clinical situations (31)(32) . In the present study one operator did all the endodontic procedures to decrease the human variability (12,13).…”
Section: Discussionmentioning
confidence: 99%